2009
DOI: 10.1159/000200084
|View full text |Cite
|
Sign up to set email alerts
|

Whole-comparative genomic hybridization in domestic sheep <i>(Ovis aries)</i> breeds

Abstract: Whole-comparative genomic hybridization (W-CGH) allows identification of chromosomal polymorphisms related to highly repetitive DNA sequences localized in constitutive heterochromatin. Such polymorphisms are detected establishing competition between genomic DNAs in an in situ hybridization environment without subtraction of highly repetitive DNA sequences, when comparing two species from closely related taxa (same species, sub-species, or breeds) or somewhat related taxa. This experimental approach was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Our results agree with data produced by Chaves et al . (2000) and by Davila-Rodriguez et al . (2009) , who found that the amount of constitutive heterochromatin is greater in all pericentromeric regions of acrocentric chromosomes than in metacentric or sex chromosomes.…”
Section: Discussionmentioning
confidence: 92%
“…Our results agree with data produced by Chaves et al . (2000) and by Davila-Rodriguez et al . (2009) , who found that the amount of constitutive heterochromatin is greater in all pericentromeric regions of acrocentric chromosomes than in metacentric or sex chromosomes.…”
Section: Discussionmentioning
confidence: 92%
“…Polymorphisms due to the accretion of duplicated genomic segments are common in mammalian genomes, in particular at centromeric and telomeric regions where they are usually silenced and show no effect on the phenotype [12][13][14][15]. In mammalian species, unexplored polymorphisms were identified in swine, sheep, stallions, and donkeys [16][17][18], and the technique also provided evidence for the presence of highly conserved repetitive DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Procedures for the identification of chromosomal polymorphisms such as whole-comparative genomic hybridization (W-CGH) or DNA breakage detection FISH (DBD-FISH) have also proven useful in phylogenetic studies between domestic sheep and the mouflon, a direct ancestor [Dávila-Rodríguez et al, 2009]. Expanding such studies to other Ovis species should improve information about the genetic diversity and evolution of the genus Ovis and complement other phylogenetics studies such as the recent study that used retroviral insertion to delineate different sheep lineages and mitochondrial lineages studies [e.g.…”
Section: Conclusion and Future Aspectsmentioning
confidence: 99%